The Role of Institutions in Supporting Parental Caregiving for Special Needs Children in Depok - Suharsiwi, Suharsiwi; Sutini, Titin; Nurhabibatulkamil, Alivia; Zikri, Muhammad; Masruroh, Riri (CV. BImbingan Belajar Assyfa, 2024)
Children with special needs often experience exclusion and marginalization, especially in access to education. Many traditional schools are not ready to accept them due to the lack of trained teachers. This forces children with special needs to travel long distances to get appropriate education. This study examines the role of institutions in providing services for children with special needs in Depok, focusing on the lack of understanding of parents in caring for children with special needs. The research method involved in-depth interviews and document analysis from various institutions that handle children with special needs in Depok. The results showed that institutions play an important role in supporting the education of children with special needs through the provision of special education facilities, teacher training, psychosocial support, and advocacy. This study emphasizes the importance of developing an adaptive education service model, supporting resources, and the crucial role of teachers in motivating and guiding children with special needs. Thus, increasing parents' understanding of their children's unique needs is a key factor in the success of these services.